Effect of availability of transcatheter aortic-valve replacement on clinical practice - Reinöhl, Jochen; Kaier, Klaus; Reinecke, Holger; Schmoor, Claudia; Frankenstein, Lutz; Vach, Werner; Cribier, Alain; Beyersdorf, Friedhelm; Bode, Christoph; Zehender, Manfred (The New England journal of medicine, 2015)
Original Article from The New England Journal of Medicine — Effect of Availability of Transcatheter Aortic-Valve Replacement on Clinical Practice
Gesehen am 17.06.2020